2013
DOI: 10.7461/jcen.2013.15.3.206
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiological Spectrum of Posterior Reversible Encephalopathy Syndrome

Abstract: ObjectiveSymptoms of posterior reversible encephalopathy syndrome (PRES) include headache, altered mental status, visual disturbances, and seizures. Typical radiological features include edema of the parieto-occipital lobes. The purpose of this study is to review the clinical and radiological findings in patients diagnosed with PRES.MethodsAll patients diagnosed with PRES between January 2006 and December 2012 were retrospectively included in this study. We reviewed demographic and clinical characteristics, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…Additionally, patients with severe hypertension are reported to have a milder vasogenic oedema than normotensive patients (20). This result would have been unexpected, if the mechanism of PRES was exclusively severe hypertension with dysfunctional autoregulation mechanisms (21). Since several patients with PRES have normal blood pressure, endothelial damage and default of the blood-brain barrier could explain the pathogenesis of the syndrome (22).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Additionally, patients with severe hypertension are reported to have a milder vasogenic oedema than normotensive patients (20). This result would have been unexpected, if the mechanism of PRES was exclusively severe hypertension with dysfunctional autoregulation mechanisms (21). Since several patients with PRES have normal blood pressure, endothelial damage and default of the blood-brain barrier could explain the pathogenesis of the syndrome (22).…”
Section: Discussionmentioning
confidence: 80%
“…FLAIR and DWI images can be helpful to distinguish vasogenic from cytotoxic oedema, the second being rather unusual in PRES lesions (12). Vasogenic oedema typically shows isointensity or hypointensity in DWI and hyperintensity on the ADC map, while cytotoxic edema shows hyperintensity in DWI and hypointensity on the ADC map (21). The presence of vasogenic oedema within the posterior arterial watershed region suggests a reversible process with a favourable prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These abnormalities demonstrate the areas of vasogenic oedema. The spared medial occipital structures help to distinguish PRES from posterior cerebral artery infarcts [11]. Abnormalities are also seen in the temporal lobes, cerebellum, basal ganglia and brain stem showing high signal on T2-weighted attenuated FLAIR sequences.…”
Section: Discussionmentioning
confidence: 93%
“…DWI shows increased diffusion in the affected regions, suggesting vasogenic edema in these areas. The preferential involvement of the parietal and occipital lobes is explained by sympathetic nervous system innervation of the posterior cerebral circulation (24,25). Fugate et al reported that the most commonly involved location in PRES was the parieto-occipital brain region (94%), followed by the frontal lobe (77%), the temporal lobe (64%), the cerebellum (53%), the basal ganglia (34%), and the brainstem (27%) (26).…”
Section: A B C D E Fmentioning
confidence: 99%